Improving seed germination and seedling growth of dragon fruit (Hylocereus undatus) by PGRs - P K, ANAGHA; D P, PRAKASHA; H, KULAPATI; MALLIKARJUN A; VIJAY M; ANAND N (The Indian Journal of Agricultural Sciences, 2024)
Dragon fruit [Hylocereus undatus (Haworth) Britton and Rose] is an exotic super fruit introduced in India. It can be naturally propagated through seeds and stem cuttings. Present study was carried out during 2018 to 2021 at Main Horticultural Research and Extension Centre (MHREC), College of Horticulture, University of Horticultural Sciences, Bagalkote, Karnataka to improve the efficiency of seed germination and seedling growth in dragon fruit using PGRs. The results showed that, there were significant differences among various treatments. Treatment 100 ppm GA3 recorded as the best treatment with respect to the parameters, viz. days taken for germination (10.60 days), germination percentage (87.00%), shoot length (10.27 cm), root length (8.06 cm), number of roots (6.20), seedling length (18.33 cm), seedling fresh weight (3.26 g), seedling dry weight (1.22 g) respectively at 90 days after sowing (DAS) and survival percentage (48%) than other treatments.